Klebsiella pneumoniae associated nosocomial meningitis in a patient after resection of meningioma. - Bhatta, Sabita; Chaudhary, Raina; Ayer, Dhirendra (Medical Journal of Shree Birendra Hospital, 2015)
Klebsiella pneumoniae is a primary pathogen capable of causing urinary tract infection (UTIs), liver abscess and pneumonia in otherwise healthy individuals. However, most infections caused by K. pneumoniae are acquired in the hospitals and/or occur in those who are debilitated by various under lying conditions. Nosocomial infections caused by K. pneumoniae includes wound infections, infections of intravascular and other invasive devices, biliary tract infections, peritonitis and meningitis. We report a case of a 29 year old male who developed meningitis after excision of meningioma. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.13004